KEPUASAN KERJA DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI KEPALA SEKOLAH SD - IIS DEWI LESTARI (Universitas Indraprasta PGRI, 2016)
The objective of this research is to verify that : (1) Job satisfaction effects on Organizational Commitment,(2)Job Satisfaction effects on Work Motivation), (3)Work Motivation effects on Organizational Commitment. The research was conducted to head master of elementary school at Duren Sawit by using survey method with path analysis applied in testing hypothesis and 50 samples selected by simple random sampling .The finding of research are : (1) There is a direct effect positive of job satisfaction on organizational commitment; (2) there is a direct effect positive of job satisfaction on work motivation; (3) there is a direct effect positive work motivation on organizational commitment. Keywords: Organizational Commitment, Job Satisfaction, Motivation